Ignition properties of thermally thin plastics: the effectiveness of non-competitive char formation in reducing flammability. Issue 3 (2002) - Nelson, M. I.; Brindley, J.; Mcintosh, A. C.
Abstract : The retardancy effect of char formation upon the ﬂammability of thermally thin products is investigated. The char is formed in a single-step non-competitive scheme and is assumed to be thermally stable. The criterion for ignition is that of a critical mass ﬂux of volatiles from the solid into the gas phase. Both steady-state and transient formulations of the model are considered. In the high activation energy limit the critical heat ﬂux efficiency in the steady-state model is proportional toc / ( 1 − c ), wherec is the fraction of char formed. In the transient model the efficiency in reducing the maximum heat release rate, average heat release rate, and total heat released is given byc and is independent of activation energy and heat ﬂux. The speciﬁc application that we have in mind for our model is piloted ignition in the cone calorimeter.